PATHOGENIC AND BIOCHEMICAL RESPONSES OF DIFFERENT CITRUS ROOTSTOCKS (Journal of Plant Disease Sciences, 2025)
Citrus is an important commercial fruit crop cultivated extensively in India, where the selection of suitable rootstocks plays a crucial role in enhancing productivity and imparting tolerance or resistance to diseases. Dry root rot, caused by Fusarium solani, is one of the most devastating diseases affecting citrus orchards. The present study was conducted to screen citrus rootstocks for resistance against dry root rot under the All India Coordinated Research Project (AICRP) on Fruit Crops at Dr. Panjabrao Deshmukh Krishi Vidyapeeth (PDKV), Akola, with the objective of identifying resistant or tolerant rootstocks. Screening was carried out using the seedling inoculation method. A total of eight citrus rootstocks, namely NRCC-1, NRCC-2, NRCC-3, NRCC-4, CRH-12, Rangpur lime, Alemow, and Jambheri, were evaluated. Among the tested rootstocks, Rangpur lime exhibited tolerance to Fusarium solani compared to the others. In addition, biochemical analyses were performed to assess defense-related parameters, including polyphenol oxidase, peroxidase, esterase activity, reducing and non-reducing sugars, and chlorophyll content. Rangpur lime recorded the highest levels of polyphenol oxidase and peroxidase activity, indicating a stronger oxidative defense response against the pathogen. The findings suggest that Rangpur lime is a promising rootstock for managing dry root rot disease in citrus cultivation.
Keywords: Biochemical analysis, Citrus, Fusarium solani, Rootstocks, Screening